ON THE BOUNDARY PROBLEM OF THE FOURTH EQUATION OF PARABOLIC- HYPERBOLIC TYPE IN PENTAGONAL DOMAIN (Scientific journal of the Fergana State University, 2023)
The present paper deals in the study of the boundary problem of the fourth order equation of the parabolic- hyperbolic type  2Lu 0 x y in pentagonal domain. The one-valued solvability of the problem is proved by the methodsof integral and differential equations.